أبعاد المسؤولية البيئية والاجتماعية في المؤسسات البترولية: دراسة ميدانية بمجمع المؤسسة الوطنية لخدمات الآبار - محسن, زوبيدة; بن الزين, حمزة; زرقون, عمر الفاروق (جامعة الوادي University of Eloued, 2016)
تهدف هذه الدراسة إلى معرفة مدى احترام المؤسسات البترولية لمبادئ وقوانين المسؤولية البيئية والاجتماعية، حيث تم اختيار المؤسسة الوطنية لخدمات الآبار (ENSP) كعينة لتطبيق هذه الدراسة من خلال توزيع مجموعة من استمارات الاستبيان قدرت بـ (130) استمارة وزعت على عمال المؤسسة ولم تستعمل كل هذه الاستمارات نظرا لإلغاء البعض منها والبعض الأخر لم يسترجع. وللوصول إلى أهداف الدراسة تم الاستعانة بمجموعة من الأدوات الإحصائية، كالمتوسط الحسابي المرجح والانحراف المعياري حيث توصلت لهذه الدراسة في الأخير إلى مجموعة نتائج نذكر منها: رغم تنوع وتعدد الآراء حول مفهوم المسؤولية الاجتماعية من تصنيفها بأنها التزام على عاتق الشركات إلى تصنيفها كذلك بأنها استجابة طوعية إلا أنها لا تخرج على كونها أعمال خيرية هادفة سواء للعمال أو للمجتمع، أن التقيد والاهتمام بمبادئ وأبعاد المسؤولية البيئية والاجتماعية لا يتنافى مع أهداف وأفاق الشركات البترولية، أن المؤسسة محل الدراسة( المؤسسة الوطنية لخدمات الآبار) لا تطبق أبعاد المسؤولية البيئية والاجتماعية. This study aims to find out how the respect of petroleum institutions to the principles and laws of environmental and social responsibility, where he was the National Foundation for wells services (ENSP) as a sample for the application of this study, through the distribution of questionnaires that was estimated at (130) form and distributed enterprise-workers did not use all of these forms due to the cancellation of some of them while others did not receive. To reach the goals of the study was used a set of statistical tools, as arithmetic weighted mean ,standard deviation, in the end we found that: despite the diversity and plurality of opinions about the concept of social responsibility of the classified as commitment to the responsibility of companies to be classified as well as a voluntary response only they do not go out on being a charity meaningful both to the workers or to the community, that compliance and attention to the principles and dimensions of environmental and social responsibility are not incompatible with the objectives and prospects of petroleum companies that the institution under our study (the national Foundation for wells) does not apply dimensions of environmental and social responsibility.
Environmental and social responsibility dimensions in the Algerian oil companies - - A field study of ENSP Group
مقال- مجلة رؤى اقتصادية
Keywords: مسؤولية البيئية، مسؤولية الإجتماعية، مؤسسات البترولية; environmental responsibility, social responsibility, petroleum enterprises